Analysis of the impact of road infrastructure development on the local economy in Pasar Sentral Subdistrict, Mimika Regency (case study: W. R. Supratman Road) - B Kresian Hutahayan; Ary Mollet; Transna Putra Urip (Studies in Economy and Public Policy, 2025)
Purpose: This study aims to analyze the impact of the W. R. Supratman Road infrastructure development on the local economy in Pasar Sentral Subdistrict, Mimika Regency, focusing on its influence on community income, business growth, and the distribution of goods and services. Research/methodology: A descriptive quantitative approach was applied, employing a paired sample t-test to compare economic indicators before and after road development. Primary data were gathered through questionnaires distributed to 30 purposively selected residents and business actors, while secondary data were obtained from government institutions. Data analysis included descriptive statistics and triangulation through interviews and field observations. Results: The findings show that road development significantly increased average household income by Rp. 683,333, improved business opportunities by 1.72 points, and enhanced the distribution of goods and services by 1.97 points. These outcomes indicate notable improvements in local economic activities after the infrastructure upgrade. Conclusions: The construction of W. R. Supratman Road positively influenced the economic conditions of the Pasar Sentral community by improving accessibility, stimulating business growth, and enhancing welfare. Better infrastructure facilitated trade flows and raised property values, supporting inclusive regional development. Limitations: The study is limited by a small sample size and short-term scope, which may not fully capture broader or long-term regional impacts. Contribution: This research provides empirical evidence of how targeted road infrastructure promotes local economic resilience and inclusive growth, offering useful insights for policymakers in regional planning.